Jurnal Penyuluhan: Perilaku Masyarakat dalam Pelestarian Hutan Mangrove di Kabupaten Pangkep Provinsi Sulawesi Selatan - Zainudin, Sumardjo, Djoko Susanto (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Mangrove forest is one natural resource which essential for the life of living creatures that lives on its surrounding. The existence of mangrove forests has become an integral part of the lives of coastal communities; hence the existence of mangrove forests should be maintained and preserved. Mangrove forest sustainability cannot be separated from the behavior of the people who live around that forest.